Damming salmon fry: evidence for predation by non‐native warmwater fishes in reservoirs. Issue 9 (21st September 2021) - Murphy, Christina A.; Romer, Jeremy D.; Stertz, Kevin; Arismendi, Ivan; Emig, Ryan; Monzyk, Fred; Johnson, Sherri L.
Abstract: Complex predator–prey interactions over time have the potential to limit survival of threatened native species. Reservoirs created by large dams in temperate ecosystems are sites where both coldwater and warmwater fish species overlap in distributions, forming assemblages that would not occur under natural settings. For example, in many western North American reservoirs, juvenile native salmonids now overlap with native and non‐native predators such as Northern Pikeminnow Ptychocheilus oregonensis and bass Micropterus spp. Currently, native Northern Pikeminnow are considered by many to be the most formidable predator of salmon smolts in freshwater systems of the Pacific Northwest. However, their consumption of salmon fry and the role of non‐native warmwater predators remain unclear. Predation on fry has proved more difficult to identify than on smolts, due to smaller sizes and high digestibility, but is important for prioritizing management strategies. Here, we use multiple lines of evidence, including large datasets of stable isotopes and fish stomach contents, to identify which fish consume Chinook Salmon Oncorhynchus tshawytscha fry (<55 mm) as they enter reservoirs below their spawning grounds in the Middle Fork Willamette River, Oregon. Unexpectedly, we found that non‐native warmwater game fishes, including bass and crappie Pomoxis spp., preyed more heavily on Chinook Salmon fry in the spring than native fish predators including Northern Pikeminnow. Of the native species, only Rainbow Trout Oncorhynchus mykiss showed evidence for significant predation on Chinook Salmon fry. Fish management in reservoirs that attempts to promote both warmwater and coldwater recreational fisheries simultaneously may thus be in conflict, necessitating future prioritization of species composition in individual reservoirs. This prioritization is especially important as these species include popular game fishes as well as salmonids threatened under the U.S. Endangered Species Act. Understanding predation pressure by popular invasive game fishes on sensitive life stages will allow managers and policymakers to evaluate trade‐offs in the management of these novel assemblages.